From politics to nostalgia – and back to politics: Tracing the shifts in the filmic depiction of the Greek 'long 1960s' over time - Kornetis, Kostis (Historein, 2014)
A number of Greek feature films in the 1990s and early 2000s – from End of an Era to Uranya – created a standard depiction of the Colonels’ dictatorship as an era filled with bittersweet adolescent memories. The Comedy of the Junta: The Light Side of a Dark Era, a recent documentary produced in April 2010 by Elias Kanellis, presented it as a laughable farce. More importantly, even, this period was treated as distant and definitely over. Almost from the onset of the economic crisis, we may say that there is a change of paradigm regarding the use of the junta and a radical departure from both the grotesque and the nostalgic view. Rather, its more brutal aspects began to be stressed in a thinly veiled attempt to highlight the continuities between past and present, the police violence and authoritarian practices of the 1967–74 era and that of the 2010–12 one – best encompassed in the popular slogan of the Indignados “The Junta did not end in ’73”. Typical examples are Fotos Lambrinos’ television documentary series It's just a junta, will it pass? and Alinda Dimitrious’s documentary The Girls of the Rain (2011). This article traces this shift and its poetics, focusing on various representative examples of both tendencies and the ways in which they sought to create a certain form of public memory.